Green Innovation Strategy in Improving Hospital Business Sustainability: A Moderation Approach in terms of Community and Customer Satisfaction at Hospitals AR. Bunda Prabumulih - Suhartati, Yayuk; Setiawan, Heri; Sayuti, Jalaludin (Universitas Muhammadiyah Yogyakarta, 2025)
The transformation of healthcare services towards sustainability is an urgent need in the face of global environmental challenges. Business sustainability in the healthcare sector is becoming increasingly important as public awareness of responsible environmental practices increases. This study aims to analyze the role of Green Innovation (GI) as an independent variable for Business Sustainability (BS), with Community and Customer Satisfaction (KM and KP) as a moderation variable in AR Bunda Hospitals. This study was conducted by adopting a quantitative approach with a survey method on respondents from the surrounding community and visits and/or families of hospital patients. The results of the study are expected to show that the implementation of Green Innovation and active community involvement are able to strengthen the role of hospitals as environmentally friendly institutions and have an impact on increasing customer satisfaction and loyalty which will have an impact on Business Sustainability. This research also contributes to the development of Green Management theory and strategic practices in sustainable hospital management in Indonesia and provides practical recommendations for the development of business strategies oriented towards environmental sustainability and community welfare.